1999
DOI: 10.1007/bf02234179
|View full text |Cite
|
Sign up to set email alerts
|

Endosonographic criteria for an internal opening of fistula-in-ano

Abstract: These combined criteria would be of particular help in performing preoperative location of an internal opening with endosonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 9 publications
2
58
1
9
Order By: Relevance
“…The presence of an internal opening was defined on the basis of the following 3 accepted criteria: hypoechoic area in the intersphincteric plane, a defect of the IAS, and a subepithelial breach connected with the intersphincteric tract through the IAS. 2,4,5 Using a soft Silastic catheter (10F Nelaton; Galmed, Bydgoszcz, Poland) introduced into the fistulaÕs tract through the external orifice, about 1 ml of 3% hydrogen peroxide solution was injected slowly into the fistulaÕs tract. After about 15 seconds, scanning of the anal canal was repeated, and the initial non-contrast study was compared with the contrast-enhanced study with regard to the type of fistula, presence of ramifications, and location of the internal opening.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of an internal opening was defined on the basis of the following 3 accepted criteria: hypoechoic area in the intersphincteric plane, a defect of the IAS, and a subepithelial breach connected with the intersphincteric tract through the IAS. 2,4,5 Using a soft Silastic catheter (10F Nelaton; Galmed, Bydgoszcz, Poland) introduced into the fistulaÕs tract through the external orifice, about 1 ml of 3% hydrogen peroxide solution was injected slowly into the fistulaÕs tract. After about 15 seconds, scanning of the anal canal was repeated, and the initial non-contrast study was compared with the contrast-enhanced study with regard to the type of fistula, presence of ramifications, and location of the internal opening.…”
Section: Methodsmentioning
confidence: 99%
“…4 Currently, the location of an internal opening has to be inferred from the following findings: the presence of a hypoechoic defect in the normally hyperechoic intersphincteric plane, a focal defect of the IAS, and a hypoechoic subepithelial breach connected with the intersphincteric tract through the IAS. 2,4,5 Using these criteria in our study, we identified 6 internal openings on non-contrast AES. However, after hydrogen peroxide injection and at surgery, only 3 of them appeared to be correctly identified [3 (27%) of 11].…”
Section: Vol 30 No 3 March/april 2002mentioning
confidence: 99%
“…Fistula tracks were visualized as tube-like, hypoechoic lesions. The internal fistula opening was identified as a hypoechoic area in the intersphincteric plane, as a defect in the internal anal sphincter, or as a subepithelial breach that connected to the fistulous tract through an internal sphincter defect [7] . After the pre-enhanced data set was saved, H2O2-enhanced sonography was performed as previously described, with some modifications [8] .…”
Section: Eausmentioning
confidence: 99%
“…The internal opening was identified on the basis of the 3 accepted criteria: hypoechoic area in the inter-sphincteric plane, a defect of the internal anal sphincter, and a subepithelial breach connected with the inter-sphincteric tract through the internal sphincter. 2,7 The presence of abscesses and their size and location in respect to the levator ani muscle were also reported. After the completion of endosonographic evaluation, a cannula was introduced through the external openings and a solution of 3% H 2 O 2 was injected.…”
Section: Methodsmentioning
confidence: 94%
“…1,3,[5][6][7] Currently, there is an increased availability of mechanical radial endosonoscopes for the diagnosis of upper gastrointestinal tract and pancreato-biliary diseases, and many practitioners use the same equipment for anorectal indications including the diagnosis of perianal fistulas. 8,9 However, a direct comparison of the two examination techniques has not been reported.…”
mentioning
confidence: 99%